The Urgency of Internalization of Minangkabau Cultural Values At Education Institutions - Ilham, Ilham; Surya Afdal, Surya (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study aims to describe the importance of internalization of Minangkabau cultural values in educational institutions. Minangkabau cultural values are the result of the social interaction of the community in the Minangkabau traditional territory which later became the adagium of Basandi Syara`, Syara` Basandi Kitabullah (ABS-SBK). The Minangkabau culture owned by the Minangkabau community is experiencing degradation, for this reason there is a need for efforts to revive it. This study uses a qualitative method with a phenomenological approach. This research is also a field work through observation stages, in-depth interviews and data analysis. Data is also obtained through literature study, namely data relevant to the research theme. The results showed that Minangkabau cultural values could be integrated into the education curriculum and one of the most effective instilling cultural values through education. Internalization is a concept of cultural education that can be done through three stages, namely transformation of values, value transactions, and trans-internalization of values.